2009
DOI: 10.3233/bmr-2009-0207
|View full text |Cite
|
Sign up to set email alerts
|

The effect of viscosupplementation on neuromuscular control of the knee in patients with osteoarthritis

Abstract: In this study, it was demonstrated that intraarticular injection of hyaluronan in patients with knee OA led to a short-term increase in proprioception and isokinetic muscle force, and also significant improvements in the functional conditions of patients. Long-term studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 25 publications
1
31
0
2
Order By: Relevance
“…The 14 studies left were reviewed in chronological order (Fig 1). 4,12,[17][18][19][20][21][22][23][24][25][26][27][28] study 1…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 14 studies left were reviewed in chronological order (Fig 1). 4,12,[17][18][19][20][21][22][23][24][25][26][27][28] study 1…”
Section: Resultsmentioning
confidence: 99%
“…Three studies suggested a statistically significant superiority of HA over placebo but for only a short period of time not exceeding 18 weeks. 24,26,27 Finally, two studies showed a modest effect in favour of HA over placebo for pain that was noticeable at six months but not for function. 23,28 Of the two studies that compared HA with steroid injections, one showed no statistically significant difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[67] In the patients who had been treated with IHA, short-term improvement in proprioception and isokinetic muscle strength along with significant improvement in function were also reported (LOE Ib). [68] In brief, the trials concernig the effects of IHA are heterogenous. Their application may provide a beneficial effect by selecting appropriate patients.…”
Section: Nonselective and Selective Nonsteroidal Antiinflammatory Drumentioning
confidence: 99%